Контроль динаміки руху подовженого контейнера - Калмыков, Михаил Александрович; Романченко, Алексей Владимирович; Яковенко, Валерий Владимирович (Eastern-European Journal of Enterprise Technologies, 2010)
The method of control of motion dynamics of the extended container with two or by a few synchronously workings vibroexciters is offered, allowing to measure the vertical and horizontal moving of container, amplitude, frequency and acceleration of motion of container